Adaptability of rabbits to the hot climate - Yamani K.A.O.; Khalil M.H. (Rabbit production in hot climates, 1994)
The rabbit as a nocturnal animal happening and being very active at night, is recommended to feed during the cool period of the nights which characterized by lower ambient temperature and lower humidity in summer months and the other hot months of the year round. The maximum and minimum temperature and the relative humidity in the morning and afternoon were analysed statistically and revealed seasonal, month, season X month significant differences. The hot months in summer and other hot months were discussed. The favourable affect of lower temperature on the performance and behaviour of the rabbit supported the proposal of the nocturnal feeding and diurnal feed utilization for rabbits under the different production systems.
1. International Conference of rabbit production in hot climates, 1994/09/06-08, Cairo (Egypt)